2017
DOI: 10.3389/fimmu.2017.00256
|View full text |Cite
|
Sign up to set email alerts
|

A Universal Vaccine against Leptospirosis: Are We Going in the Right Direction?

Abstract: Leptospirosis is the most widespread zoonosis in the world and a neglected tropical disease estimated to cause severe infection in more than one million people worldwide every year that can be combated by effective immunization. However, no significant progress has been made on the leptospirosis vaccine since the advent of bacterins over 100 years. Although protective against lethal infection, particularly in animals, bacterin-induced immunity is considered short term, serovar restricted, and the vaccine can c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 96 publications
0
55
0
1
Order By: Relevance
“…This technique has recently been implemented for leptospires (for comprehensive recent reviews see Refs. [75] and [76]). In 2006, the Yang group obtained the first results using bioinformatics and analysis based on the theory of reverse vaccinology.…”
Section: Reverse and Structural Vaccinology (Rv)mentioning
confidence: 98%
See 1 more Smart Citation
“…This technique has recently been implemented for leptospires (for comprehensive recent reviews see Refs. [75] and [76]). In 2006, the Yang group obtained the first results using bioinformatics and analysis based on the theory of reverse vaccinology.…”
Section: Reverse and Structural Vaccinology (Rv)mentioning
confidence: 98%
“…Among these proteins, the conserved orthologs present in all the pathogenic serovars, harboring outer membrane b barrel domains, were further modeled in 3D. Peptides predicted to be surface exposed epitopes of major histocompatibility complex of class II molecules were mapped on the proteins, giving information about their potential immunogenicity [80,76]. This study identified 18 outer membrane proteins, including 8 outer membrane lipoproteins, TolC efflux pumps and several TonB-dependent transporters, that bind and transport siderophores, metals, and vitamins [80].…”
Section: Reverse and Structural Vaccinology (Rv)mentioning
confidence: 99%
“…The exploration of recombinant strategies can be particularly fruitful when classical vaccine strategies provide weak protection. Currently available inactivated vaccines against leptospirosis, the most common bacterial zoonosis ( Picardeau, 2017 ), are inadequate because of the severe side-effects and lack of cross-protection among pathogenic Leptospira species ( Grassmann et al, 2017 ; Adler, 2015 ). Because the estimated worldwide burden of leptospirosis is over 1 million severe cases and ~60,000 deaths per year, advances in recombinant leptospiral vaccines are desperately needed and are likely to benefit from a structure-based antigen design strategy ( Picardeau, 2017 ; Costa et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…While several leptospiral antigens have been explored for use in vaccines, the most promising candidates have been derived from the Leptospira immunoglobulin-like (Lig) protein family ( Ko et al, 2009 ; Grassmann et al, 2017 ; Cao et al, 2011 ; Yan et al, 2009 ; Chang et al, 2007 ). Lig proteins are present in only pathogenic species with LigB (but not LigA or LigC) being found in all pathogenic Leptospira genomes ( McBride et al, 2009 ; Matsunaga et al, 2003 ), LigB’s expression during host invasion further suggests an important role in virulence ( Lessa-Aquino et al, 2017 ; Choy et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Existing commercial vaccines rely on inactivated or fragmented Leptospira spp. bacteria and have a high potential for severe side effects (Adler, ; Grassmann, Souza, & McBride, ). Proteins displayed on the leptospiral surface during host infection provide an optimal target for recombinant vaccines (Chang et al, ; Dellagostin et al, ; Lessa‐Aquino et al, ).…”
Section: Introductionmentioning
confidence: 99%